Multi-sensor satellite remote sensing of volcanic regions - Way, Lin (Nanyang Technological University, 2021)
Volcano monitoring is important for understanding the current activity level and potential for eruption. While ground-based monitoring is still necessary for temporally dense monitoring, satellite data is increasingly used for monitoring regional volcanic activity and processes due to its wider spatial footprint and coverage over remote volcanoes (Pritchard et al., in press). Satellite-based techniques have been used to monitor deformation, thermal features, gas emissions and ash emissions. In this study, we focus on satellite detections of thermal anomalies (Part I) and deformation (Part II). Numerous studies have made use of thermal observations from satellite data to analyse a range of volcanic features including lava flows and fumarole fields (Pyle et al., 2013). In comparison to conventional point-based deformation measurements, advancements in Interferometric Synthetic Aperture Radar (InSAR) techniques provide spatially dense surface deformation data which can be used to model and gain insights into underlying volcanic or tectonic processes (Pyle et al., 2013). Each type of volcanic monitoring has different temporal and spatial resolutions as well as thresholds for detection (Furtney et al., 2018). Together with the fact that not all volcanoes show all types of activity at the same time, this suggests a need for integration between multiple datasets and sensors. While thermal observations from infrared measurements by MODIS (Moderate Resolution Imaging Spectroradiometer) can be acquired up to four times a day at 1 km/pixel, ASTER (Advanced Spaceborne Thermal Emission and Reflection Radiometer) has a longer repeat interval of at least 16 days but with higher spatial resolution (90 m/pixel). Data from MODIS and ASTER are complementary and can reveal volcanic processes that occur over different time and spatial scales. In this report, we use two different types of satellite data in two separate geographic areas to address the following research questions: 1. What proportion of Indonesian volcanoes have satellite detectable thermal anomalies, as compared to volcanoes located in other volcano-rich countries such as the United States? (Part I) 2. What is the nature of volcano-tectonic interactions around Sabancaya volcano in Peru? (Part II) We show that there is potential in using higher resolution thermal infrared data to identify and track changes in volcanic thermal features at potentially active volcanoes, and higher coherence InSAR data can reveal more detailed surface deformation and lead to fault source models that are more representative of the regional tectonics.